Body weight and body mass index influence bone mineral density in late adolescence in a two-year follow-up study. The Tromsø Study: Fit Futures - Nilsen, Ole Andreas; Ahmed, Luai A.; Winther, Anne; Christoffersen, Tore; Thrane, Gyrd; Evensen, Elin; Furberg, Anne-Sofie; Grimnes, Guri; Dennison, Elaine; Emaus, Nina (JBMR Plus, 2019)
Determinants of bone acquisition in late adolescence and early adulthood are not well‐described. This 2‐year follow‐up study explored the associations of body weight (BW), body mass index (BMI), and changes in weight status with adolescent bone accretion in a sample of 651 adolescents (355 girls and 296 boys) between 15 and 19 years of age from The Tromsø Study: Fit Futures. This Norwegian population‐based cohort study was conducted from 2010 to 2011 and was repeated from 2012 to 2013. We measured femoral neck, total hip, and total body bone mineral content and areal bone mineral density (aBMD) by dual‐energy X‐ray absorptiometry. We measured height, BW, calculated BMI (kg/m 2 ), and collected information on lifestyle at both surveys. Mean BMI (SD) at baseline was 22.17 (3.76) and 22.18 (3.93) in girls and boys, respectively. Through multiple linear regression, baseline BW and BMI were positively associated with ∆aBMD over 2 years of follow‐up at all skeletal sites in boys ( p < 0.05), but not in girls. ∆BW and ∆BMI predicted ∆aBMD and ∆BMC in both sexes, but the strength of the associations was moderate. Individuals who lost weight during follow‐up demonstrated a slowed progression of aBMD accretion compared with those gaining weight, but loss of BW or reduction of BMI during 2 years was not associated with net loss of aBMD. In conclusion, our results confirm that adequate BW for height in late adolescence is important for bone health. Associations between change in weight status and bone accretion during follow‐up were moderate and unlikely to have any clinical implication on adolescents of normal weight. Underweight individuals, particularly boys, are at risk of not reaching optimal peak bone mass and could benefit from an increase in BMI.